Immediate and Delayed Micro Tensile Bond Strength of Different Bioactive Restorative Materials - Ahmed Tharwat Al Ammary; Saad ElSayed Abd ElNaby Nawaya; Amir Hussieny Abd El Hamid Ibrahim; Mahmoud Elsayed Fetouh; Hatem Abdul Monaem El bially; Ahmed Ali Ezzeldine; Ahmed Mohamed Abu siyam; Walaa Mohamed Ahmed Alsamoully; Ibrahim El Dossoky Basha; Ahmed Ali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aim:The current research aimed to assess the immediate and delayed the micro tensile bond strength (μ-tbs) of three bioactive restorative materials (Surefil one, Cention forte, and Fuji II LC). Method:60 human permanent lower molars were used in this study. The teeth have decoronated 4 mm coronal to cementoenamel junction. The pulp chamber of each tooth was accessed by taper stone bure with high-speed hand piece for making place for placing the tested filling materials.The Specimens were randomized divided into 3 main identical test groups with 20 teeth in each main group according to the kind of the tested restoration then every group was subdivided into 2 subgroups according to the time of evaluation with 10 teeth each (immediate and delayed). Group 1: Surefil one, Group 2: Cention forte, and Group 3: Fuji II LC. The teeth were prepared for the μ-TBS test to be assessed immediate after restoration and the other teeth after storage time 6 months. The immediate test samples were tested after 48 hours of filling the materials, while the delayed test samples were stored in artificial saliva for 6 months. Results: In concerning the immediate test results: showed that the greatest μ-TBS was recorded in group 3 Fuji II LC 19.9 ± 4.6, then Group 1 Surefil one recorded 10 ± 3.2, while group 2 Cention forte recorded the lowest μ-TBS mean values 8.8 ± 2.8. Statistically, there was statistically insignificant variation across the groups 1&2 (P > 0.05). on other hand there was statistically significant difference in comparing group 3 with groups 1 & 2 (P < 0.05). While In concerning the delayed test results: showed in concerning the delayed test results: showed that the greatest μ-TBS was recorded in Group 1 Surefil one recorded 8.9 ± 2.8, thengroup 2 Cention forte 7.4 ± 2.9, while group 3 Fuji II LC recorded the lowest μ-TBS mean values 7 ± 1.9. Statistically, there was statistically insignificant variation across all groups 1,2, and 3 (P > 0.05). There was statistically insignificant variation when comparing between the results of Immediate versus Delayed results of groups 1&2 (P > 0.05). on other hand there was statistically significant difference in comparing the results of group 3 between the immediate and delayed results (P < 0.05). Conclusion:The durability and good μ-TBS results of self-adhesive bulk-fill dental restoration make them the good choice for teeth restoration.